Slurry for electronic-grade glass fiber cloth as well as preparation method, product and application of slurry

By using water-soluble polyester main film forming agent, polypropylene glycol auxiliary film forming agent and other combination components in the slurry of electronic grade glass fiber cloth, the problems of high defects, poor wear resistance and poor desorption during weaving are solved, and the problems of high defects, poor wear resistance and poor desorption during weaving are achieved. High-performance fiberglass fabric production, with excellent weaving properties and low ash properties.

CN119243477APending Publication Date: 2025-01-03JUSHI GRP CO
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411292006.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The problems of high warp defects, poor wear resistance and poor desizing during the weaving process of electronic grade fiberglass cloth affect its weaving performance and the yield rate of downstream products.

Method used

The slurry is used to improve the cladding of the slurry of water-soluble polyester main film forming agent, polypropylene glycol auxiliary film forming agent, combustion aid, lubricant, antistatic agent and defoaming agent. , clustering and desizing properties, reduce ash content, and improve the weaving performance and breathability of glass fibers.

Benefits of technology

It significantly reduces defects and ash during the weaving process, improves the wear resistance and weaving performance of glass fibers, and improves the desizing effect. The electronic-grade glass fiber cloth produced has low breathability and high impregnation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005044881450000021
    Figure BDA0005044881450000021
  • Figure BDA0005044881450000031
    Figure BDA0005044881450000031
  • Figure BDA0005044881450000032
    Figure BDA0005044881450000032
Patent Text Reader

Abstract

The invention provides slurry for electronic-grade glass fiber cloth, the slurry is an aqueous solution and comprises effective components and water, and the effective components are respectively a water-soluble polyester main film-forming agent, a polypropylene glycol auxiliary film-forming agent, a combustion improver, a lubricant, an antistatic agent and a defoaming agent; the mass percentage of each component in the total mass of the slurry is as follows: 2.0 to 35.0 percent of a water-soluble polyester main film-forming agent, 0.5 to 13.0 percent of a polypropylene glycol auxiliary film-forming agent, 0.1 to 3.0 percent of a combustion improver, 0.03 to 1.5 percent of a lubricant, 0.02 to 1.2 percent of an antistatic agent, 0.005 to 1.0 percent of a defoaming agent and 60.0 to 97.0 percent of water. The coating property and bundling property of the sizing agent in the glass fiber can be improved, the interface bonding degree of the sizing agent and the glass fiber is improved, warp-direction weaving defects of a cloth cover are reduced, and the weaving performance of the glass fiber is improved; the sizing agent has good desizing performance and low ash content, and the produced electronic cloth has the advantages of being low in air permeability, good in impregnation performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electronic-grade glass fiber cloth slurry, and specifically relates to a slurry for electronic-grade glass fiber cloth and a preparation method, product and application thereof. Background Art

[0002] Electronic grade glass fiber cloth (referred to as electronic cloth) is mainly used in the electronic industry such as copper clad laminate (CCL) and printed circuit board (PCB). The industry has extremely high requirements for the apparent quality and performance of the product. The sizing agent is designed and developed for the warp yarn bundle of the electronic cloth. It plays an important role in chemical bundling and reinforcement in the transition of the electronic yarn bundle to the fabric of the electronic cloth. It reduces the friction of the weft yarn on the warp yarn during the plain weave of the air jet loom. After weaving, the sizing is removed in the post-processing process, and the ash left behind directly affects the coating effect of the post-treatment agent on the glass fiber, and has an effect on the performance of the electronic cloth in the downstream copper clad laminate.

[0003] The selection of chemical composition of the slurry in the production process of electronic-grade glass fiber cloth is extremely critical. Due to the characteristics of polymers, the slurry has a certain coating and strengthening effect in the yarn sizing, which is reflected in the wear resistance during the weaving process of the loom. Yarn bundles with good slurry coating effect can effectively reduce the phenomenon of fuzzing on the surface of the glass fiber and prevent the generation of broken wires. After the glue is applied on the copper-clad laminate client, the surface is smooth and free of glue particles, and can be directly used as commercial film processing; if the electronic-grade glass fiber cloth has more hairiness and broken wires, it will not be able to cover the use of takeaway commercial films and high-end products. Therefore, the coating effect of the slurry of the electronic cloth has a great influence on the performance of the product.

[0004] The current electronics industry has extremely high requirements for electronic-grade glass fiber cloth, especially the ash content of the sizing agent and slurry remaining on the electronic cloth after desizing is relatively high, which is not conducive to the combination of the post-treatment agent and the glass fiber, thus having a great impact on the wetting performance and interface bonding performance of the electronic cloth; in addition, the slurry has a direct relationship with the weaving performance of the electronic-grade glass fiber cloth and the apparent defects produced, affecting the yield of downstream copper-clad laminate products. In order to solve the above problems, it is urgent to develop high-performance electronic-grade glass fiber slurry.

[0005] Chinese patent CN 113584886 A discloses a sizing material for secondary sizing of warp yarns of electronic glass fiber cloth and its preparation method, which uses components such as rosin resin film-forming agent, and the film formed by the sizing material has better coating and wear resistance, and the sizing condition is significantly improved, and the number of quality defects such as hairiness and broken ends in production is also reduced. However, the rosin resin film-forming agent added in the patent has a high boiling point, which is not conducive to desizing, produces a high ash content, and brings about desizing pollution, and may lead to reduced performance of electronic-grade glass fiber products.

[0006] Chinese patent CN 108726897 A discloses a secondary sizing agent for electronic grade glass fiber yarn, glass fiber yarn sized therewith and corresponding glass fiber cloth, and studies the use of polyvinyl alcohol, waterborne polyurethane, polyethylene glycol and lubricant. The obtained secondary sizing agent can not only protect the warp yarn to meet the requirements of high-speed weaving process, but also has the performance characteristics of less residual fat after thermal burning. However, polyvinyl alcohol is still used as the main film-forming agent in the sizing agent of the patent, which is not conducive to desizing and produces extremely high energy consumption; and the sizing agent is prone to adsorption and entanglement in glass fiber production; and polyvinyl alcohol and waterborne polyurethane sizing agent are prone to changes in sizing composition and content, causing pollution to yarn and machine, thereby affecting the quality stability of glass fiber products. Summary of the invention

[0007] The present application aims to solve the problems of high warp defects, poor wear resistance, and poor desizing of electronic-grade glass fiber cloth during weaving, and to provide an electronic-grade glass fiber cloth slurry and a preparation method thereof. The present application can improve the coating and bundling properties of the slurry in the glass fiber, enhance the degree of interface bonding between the slurry and the glass fiber, reduce the warp weaving defects on the cloth surface, and improve the weaving performance of the glass fiber. In addition, the slurry of the present application has good desizing properties and a low ash content, and the electronic cloth produced has the advantages of low air permeability and good impregnation performance.

[0008] According to one aspect of the present application, a slurry for electronic grade glass fiber cloth is provided, wherein the slurry is an aqueous solution, comprising effective ingredients and water, wherein the effective ingredients are respectively a water-soluble polyester main film-forming agent, a polypropylene glycol auxiliary film-forming agent, a combustion aid, a lubricant, an antistatic agent and a defoaming agent; the mass of each component in the total mass of the slurry is expressed as follows:

[0009]

[0010] Furthermore, the mass of each component accounts for the percentage of the total mass of the slurry:

[0011]

[0012] The water-soluble polyester main film-forming agent is a water-soluble high molecular polyester resin formed by polycondensation of diols and dibasic acids.

[0013] Furthermore, the diol is one of diethylene glycol, triethylene glycol, polyethylene glycol, or a mixture of any two of them.

[0014] Furthermore, the dibasic acid is maleic anhydride, adipic acid or a mixture of the two.

[0015] Furthermore, the polypropylene glycol auxiliary film-forming agent is one of polypropylene glycol PPG-400, polypropylene glycol PPG-600, polypropylene glycol PPG-2000, or a mixture of any of them.

[0016] Furthermore, the combustion improver is one of polyethylene oxide and polyacrylamide or a mixture of the two.

[0017] Furthermore, the lubricant is one of dioctadecyl dimethyl ammonium chloride, aqueous paraffin, and hydroxyethyl cellulose, or a mixture of any of them.

[0018] Furthermore, the antistatic agent is one of sorbitol and fatty amine polyoxyethylene ether or a mixture of the two.

[0019] Furthermore, the defoaming agent is water-based modified polydimethylsiloxane.

[0020] Furthermore, in the electronic-grade glass fiber cloth slurry, the mass of each component accounts for the percentage of the total mass of the slurry:

[0021]

[0022]

[0023] The water-soluble polyester main film-forming agent is a diol and a dibasic acid type water-soluble high molecular polyester resin, which can be prepared according to conventional methods in existing literature. The diol is one of diethylene glycol, triethylene glycol, polyethylene glycol or a mixture of any of them. The dibasic acid is one of maleic anhydride and adipic acid or a mixture of the two.

[0024] The water-soluble polyester main film-forming agent of the present application has excellent coating and bundling properties for glass fibers, and good adhesion can improve the wear resistance of glass fibers. An appropriate amount of polyester film-forming agent can effectively reduce the generation of fuzz and broken fibers in the weaving process of glass fibers, and improve the quality of the cloth surface. A water-soluble polyester film-forming agent with a low content is not effective in coating and film-forming glass fibers, and has poor wear resistance; while a high content will lead to excessive bundling, which is not conducive to the opening of the electronic cloth, making the air permeability of the electronic cloth too high and reducing the infiltration speed of the downstream resin.

[0025] Wherein, the polypropylene glycol auxiliary film-forming agent is one or a mixture of any of polypropylene glycol PPG-400, polypropylene glycol PPG-600, and polypropylene glycol PPG-2000. As a film-forming agent, polypropylene glycol can improve the smoothness of the glass fiber in the desizing process and has antistatic properties. When combined with polyester resin, it can further improve the film-forming and weaving properties of the glass fiber. The amount of polypropylene glycol added needs to be controlled within an appropriate range. Too little auxiliary film-forming agent cannot achieve the dispersion and softening effect of the yarn bundle, which is not conducive to the flattening degree of the electronic cloth yarn bundle; and too much auxiliary film-forming agent added will make the organic content of the yarn bundle higher, and the cost of energy consumption required for desizing will increase.

[0026] Wherein, the combustion improver is one of polyethylene oxide and polyacrylamide or a mixture of the two. The use of a combustion improver is an important innovation of this application. The addition of a combustion improver can effectively reduce the ash content of the glass fiber cloth, thereby improving the wettability and interface bonding strength of the glass fiber cloth and downstream products, and improving the performance of the glass fiber cloth. The selected polyethylene oxide and / or polyacrylamide dissolves, swells and disperses evenly in the aqueous solution, so that the slurry can be fully burned during desizing, reducing carbon deposition and improving the desizing rate. Furthermore, it is necessary to strictly control the amount of the combustion improver added to the slurry. Too little combustion improver has no significant effect on the overall desizing of the slurry, and the ash content is still high; and too much flame retardant will affect the coating and bundling of the slurry on the glass fiber, and affect the quality of the glass fiber. Therefore, in this application, adding 0.1 to 3.0% of a combustion improver can well improve the desizing performance of the slurry.

[0027] Wherein, the lubricant is one of dioctadecyl dimethyl ammonium chloride, aqueous paraffin, hydroxyethyl cellulose or a mixture of any of them. The addition of lubricant can effectively improve the phenomenon of broken fibers caused by friction of glass fibers in the weaving path, increase the smoothness of glass fibers in the weaving process, and reduce the apparent defects of glass fiber cloth. The lubricant needs to be added to the slurry in an appropriate amount. Too little lubricant has no significant lubricating effect during the weaving process of the yarn bundle, and the glass fibers are easily damaged and fluffed during weaving; while too much lubricant will affect the film-forming property of the slurry on the glass fibers and affect the desizing property.

[0028] Wherein, the antistatic agent is one of sorbitol, fatty amine polyoxyethylene ether or a mixture of the two. Electronic grade glass fiber belongs to fine yarn in the category of glass fiber, and the single fiber diameter is 9 microns or less, which is prone to electrostatic effect. By adding antistatic agent, the antistatic property of glass fiber is improved, and the undesirable phenomena such as yarn breakage and yarn output disorder caused by glass fiber adsorption and entanglement are avoided. The amount of antistatic agent added needs to be strictly controlled. Too little antistatic agent has insufficient antistatic effect on yarn, and yarn bundle adsorption and entanglement are prone to occur; while too much antistatic agent can easily deteriorate the bundling of yarn bundles, which affects the weaving performance of glass fiber.

[0029] Wherein, the defoaming agent is water-based modified polydimethylsiloxane. During the machine production process, the slurry is prone to foaming, which will affect the uniformity of the slurry, and the overflow of foam will affect the production machine. By adding a defoaming agent, the generation and accumulation of foam during the use of the slurry can be reduced, and the slurry can be evenly and effectively coated on the glass fiber. The amount of defoaming agent added to the slurry needs to be appropriate. Too little defoaming agent will not have a significant effect on eliminating foam, and will still produce more foam to affect the operation of the machine; and the addition of too much defoaming agent will affect the coating effect of the film-forming agent in the slurry on the yarn bundle, thereby affecting the quality of the electronic cloth.

[0030] According to a second aspect of the present application, a method for preparing the aforementioned electronic-grade glass fiber cloth slurry is provided, comprising the following steps:

[0031] 1. Add a certain amount of water into the container, and add the water-soluble polyester main film-forming agent while stirring;

[0032] 2. Raise the temperature to 50-90°C and keep the temperature constant for 30-60 minutes to form a first stable and uniform slurry;

[0033] 3. Add polypropylene glycol auxiliary film-forming agent, maintain constant temperature for at least 30 minutes under stirring to form a second stable uniform slurry;

[0034] 4. Add combustion aid, lubricant, antistatic agent and defoaming agent, keep constant temperature for 20-40 minutes to form the third stable uniform slurry;

[0035] 5. Make up the remaining water and control the constant temperature at 40℃-70℃ to obtain electronic grade glass fiber cloth slurry.

[0036] Among them, water is preferably deionized water.

[0037] According to a third aspect of the present application, there is provided a glass fiber product having a glass fiber diameter of 9 microns or less produced from the aforementioned electronic-grade glass fiber cloth slurry.

[0038] According to a fourth aspect of the present application, there is provided application of the aforementioned glass fiber product in the field of manufacturing copper clad laminates and printed circuit boards.

[0039] This application is based on a large number of laboratory research and production applications. The innovative use of a combination of a water-soluble polyester main film-forming agent and a polypropylene glycol auxiliary film-forming agent can improve the coating and bundling properties of electronic-grade glass fibers and improve weaving performance; with a suitable combustion aid, the desizing performance of the slurry is improved, thereby improving the impregnation of the electronic-grade glass fiber cloth; in addition, with appropriate lubricants, antistatic agents and defoaming agents, the friction and broken wires of the glass fibers in the weaving path can be reduced, and the broken yarns and unsmooth yarn output can be reduced, and the usability of the slurry can be stabilized. By rationally configuring the types and contents of each component, the slurry for electronic-grade glass fibers of this application is suitable for the production of glass fibers with a single fiber diameter of 9 microns or less, and can solve problems such as high defects, poor wear resistance, and poor desizing. Compared with the existing slurry production of glass fiber cloth, it has the advantages of excellent weaving performance, few apparent defects, and good desizing, and has a lower ash content. The electronic-grade glass fiber cloth produced has the advantages of low air permeability and good impregnation performance. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be arbitrarily combined with each other.

[0041] The electronic grade glass fiber cloth slurry of the present application is an aqueous solution, including effective ingredients and water, wherein the effective ingredients are respectively a water-soluble polyester main film-forming agent, a polypropylene glycol auxiliary film-forming agent, a combustion aid, a lubricant, an antistatic agent and a defoaming agent; the mass of each component in the total mass of the slurry is expressed as follows:

[0042] 2.0-35.0% water-soluble polyester main film-forming agent, 0.5-13.0% polypropylene glycol auxiliary film-forming agent, 0.1-3.0% combustion aid, 0.03-1.5% lubricant, 0.02-1.2% antistatic agent, 0.005-1.0% defoaming agent, 60.0%-97.0% water.

[0043] Preferably, the mass of each component accounts for the percentage of the total mass of the slurry:

[0044] 3.0-25.0% water-soluble polyester main film-forming agent, 0.8-9.0% polypropylene glycol auxiliary film-forming agent, 0.3-2.5% combustion aid, 0.15-1.2% lubricant, 0.05-0.8% antistatic agent, 0.02-0.6% defoaming agent, 72.0%-96.5% water.

[0045] More preferably, the mass of each component accounts for the percentage of the total mass of the slurry:

[0046] 3.0-22.0% water-soluble polyester main film-forming agent, 1.0-8.5% polypropylene glycol auxiliary film-forming agent, 0.4-2.3% combustion aid, 0.20-1.1% lubricant, 0.08-0.7% antistatic agent, 0.03-0.6% defoaming agent, 75.0%-96.0% water.

[0047] The water-soluble polyester main film-forming agent is a water-soluble high molecular polyester resin formed by condensation of diol and dibasic acid; the diol is one of diethylene glycol, triethylene glycol, polyethylene glycol or a mixture of any of them; the dibasic acid is one of maleic anhydride and adipic acid or a mixture of the two.

[0048] The polypropylene glycol auxiliary film-forming agent is one of polypropylene glycol PPG-400, polypropylene glycol PPG-600, polypropylene glycol PPG-2000 or a mixture of any of them.

[0049] The combustion aid is one of polyethylene oxide and polyacrylamide or a mixture of the two.

[0050] The lubricant is one of dioctadecyl dimethyl ammonium chloride, aqueous paraffin, and hydroxyethyl cellulose or a mixture of any of them.

[0051] The antistatic agent is one of sorbitol and fatty amine polyoxyethylene ether or a mixture of the two.

[0052] The defoamer is water-based modified polydimethylsiloxane.

[0053] The water is deionized water. The method for preparing the slurry for electronic grade glass fiber cloth comprises the following steps:

[0054] 1. Add a certain amount of water into the container, and add the water-soluble polyester main film-forming agent while stirring;

[0055] 2. Raise the temperature to 50-90°C and keep the temperature constant for 30-60 minutes to form a first stable and uniform slurry;

[0056] 3. Add polypropylene glycol auxiliary film-forming agent, maintain constant temperature for at least 30 minutes under stirring to form a second stable uniform slurry;

[0057] 4. Add combustion aid, lubricant, antistatic agent and defoaming agent, keep constant temperature for 20-40 minutes to form the third stable uniform slurry;

[0058] 5. Make up the remaining water and control the constant temperature at 40℃-70℃ to obtain electronic grade glass fiber cloth slurry.

[0059] Table 1 below lists the specific formulas of some preferred embodiments 1 to 6 of the slurry for electronic grade glass fiber cloth of the present application.

[0060] Table 1 Specific formula of the slurry in the embodiment

[0061]

[0062]

[0063] Table 1 Specific formula of slurry in Example (continued)

[0064]

[0065]

[0066] The preparation method of the slurry for electronic grade glass fiber cloth in embodiments 1 to 12 comprises the following steps: 1. adding 65% of the total amount of deionized water into a container, and adding water-soluble polyester under stirring;

[0067] 2. Raise the temperature to 80°C and keep the temperature constant for 50 minutes to form the first stable and uniform slurry;

[0068] 3. Add polypropylene glycol, keep the temperature constant for 40 minutes under stirring to form a second stable uniform slurry; 4. Add a combustion improver, a lubricant, an antistatic agent, and a defoaming agent, keep the temperature constant for 30 minutes to form a third stable uniform slurry;

[0069] 5. Make up the remaining amount of deionized water, control the constant temperature at 60°C, and obtain the slurry for electronic grade glass fiber cloth.

[0070] In order to better explain the effect of the present application, two conventional slurries suitable for electronic grade glass fibers are selected as comparative samples (Comparative Example 1 and Comparative Example 2). The content of each component of the glass fiber electronic cloth slurry is expressed in weight percentage:

[0071] Comparative Example 1:

[0072] The content and mass percentage of each component are expressed as follows:

[0073] Polyvinyl alcohol: 4.75%

[0074] Modified starch: 1.62%

[0075] Polyethylene glycol: 3.13%

[0076] Acrylate: 0.56%

[0077] Sodium dodecyl sulfate: 0.18%

[0078] Deionized water: 89.76%

[0079] Comparative Example 2:

[0080] The content and mass percentage of each component are expressed as follows:

[0081] Polyvinyl alcohol: 3.23%

[0082] Modified starch: 2.39%

[0083] Polyethylene glycol: 2.86%

[0084] Acrylate: 1.82%

[0085] Sodium dodecyl sulfate: 0.13%

[0086] Deionized water: 91.57%

[0087] Wherein, the preparation method of comparative examples 1 to 2 comprises the following steps:

[0088] 1. Add 65% of the total amount of deionized water into the container, and add polyvinyl alcohol while stirring;

[0089] 2. Raise the temperature to 90°C, keep the temperature constant for 30 minutes, add modified starch, and stir for 20 minutes to form a stable and uniform slurry;

[0090] 3. Add acrylate and sodium dodecyl sulfate, and keep the temperature constant for 30 minutes under stirring to form a stable and uniform slurry;

[0091] 4. Add 15% of the total amount of deionized water, control the temperature to 70°C, add polyethylene glycol, and maintain the constant temperature for 30 minutes to form a stable and uniform slurry;

[0092] 5. Add the rest of the deionized water and control the constant temperature at 60°C to obtain electronic grade glass fiber cloth slurry.

[0093] The present application conducted comparative tests on the performance of Examples 1 to 12 and Comparative Examples 1 to 2, and the test method is as follows:

[0094] The slurries of Examples 1 to 12 and Comparative Examples 1 to 2 were respectively coated on electronic-grade glass fiber products with 400 single fibers and a single fiber diameter of 9 microns using a slurry machine, and electronic-grade glass fiber cloth products were produced using a paralleling machine, a loom, and primary desizing, secondary desizing and surface treatment.

[0095] Table 2 Test results of various embodiments and comparative examples

[0096]

[0097] Table 2 Test results of various embodiments and comparative examples (continued)

[0098]

[0099]

[0100] The test results in Table 2 show that the electronic-grade glass fiber produced by the slurry for electronic-grade glass fiber cloth of the present application and the preparation method thereof has a warp yarn sizing rate of 2.42% to 3.96%. The number of fuzzing defects per 10,000 meters of the present application embodiment is 0.63 to 1.47 per 10,000 meters, which is significantly lower than the 3.67 per 10,000 meters and 3.28 per 10,000 meters of Comparative Examples 1 and 2, and the number of defects in the total 10,000 meters of the warp direction is 2.37 to 3.62 per 10,000 meters, which is also greatly reduced compared with the defects of Comparative Examples 1 and 2. The weaving performance and wear resistance of the electronic-grade glass fiber cloth are significantly improved. The primary desizing ash and secondary desizing ash of the present application embodiment are 0.126% to 0.206% and 0.028% to 0.042% respectively, which are significantly lower than the primary desizing ash and secondary desizing of Comparative Examples 1 to 2. The slurry of the present application embodiment has better desizing performance. The warp tensile strength of Examples 1 to 12 is higher than that of Comparative Examples 1 to 2, and the air permeability and impregnation time are lower than those of Comparative Examples 1 to 2, indicating that the electronic-grade glass fiber cloth produced by the electronic-grade glass fiber cloth slurry and the preparation method thereof of the present application has better mechanical properties and impregnation properties, which is beneficial to the electronic-grade glass fiber cloth and downstream resin penetration and mechanical property improvement.

[0101] In summary, the slurry for electronic-grade glass fiber cloth and the preparation method thereof provided in the present application can improve the coating and bundling properties of the slurry in the glass fiber, enhance the interface bonding between the slurry and the glass fiber, and make the glass fiber have excellent weaving performance, fewer surface defects, good desizing properties, and lower ash content. The produced electronic-grade glass fiber cloth has the advantages of low air permeability and good impregnation performance.

[0102] It should be noted that, in the present application, the solid mass of each effective component refers to the mass of non-aqueous substances in each effective component, and is not limited to the solid component.

[0103] Finally, it should be noted that in this article, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.

[0104] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A slurry for electronic grade glass fiber cloth, characterized in that: The slurry is an aqueous solution, including active ingredients and water, wherein the active ingredients are respectively a water-soluble polyester main film-forming agent, a polypropylene glycol auxiliary film-forming agent, a combustion aid, a lubricant, an antistatic agent and a defoaming agent; the mass of each component in the total mass of the slurry is expressed as follows:

2. The electronic grade glass fiber cloth slurry according to claim 1, characterized in that: The percentage of the mass of each component to the total mass of the slurry is:

3. The electronic grade glass fiber cloth slurry according to claim 1 or 2, characterized in that: The water-soluble polyester main film-forming agent is a water-soluble high molecular polyester resin formed by polycondensation of diol and dibasic acid.

4. The electronic grade glass fiber cloth slurry according to claim 3, characterized in that: The diol is one of diethylene glycol, triethylene glycol, polyethylene glycol or a mixture of any of them.

5. The electronic grade glass fiber cloth slurry according to claim 3, characterized in that: The dibasic acid is maleic anhydride, adipic acid or a mixture of the two.

6. The electronic grade glass fiber cloth slurry according to claim 1 or 2, characterized in that: The polypropylene glycol auxiliary film-forming agent is one of polypropylene glycol PPG-400, polypropylene glycol PPG-600, polypropylene glycol PPG-2000, or a mixture of any of the above.

7. The electronic grade glass fiber cloth slurry according to claim 1 or 2, characterized in that: The combustion improver is one of polyethylene oxide and polyacrylamide or a mixture of the two.

8. The electronic grade glass fiber cloth slurry according to claim 1 or 2, characterized in that: The lubricant is one of dioctadecyl dimethyl ammonium chloride, aqueous paraffin, and hydroxyethyl cellulose, or a mixture of any of the above.

9. The electronic grade glass fiber cloth slurry according to claim 1 or 2, characterized in that: The antistatic agent is one of sorbitol and fatty amine polyoxyethylene ether or a mixture of the two.

10. The electronic grade glass fiber cloth slurry according to claim 1 or 2, characterized in that: The defoamer is water-based modified polydimethylsiloxane.

11. The method for preparing the slurry for electronic grade glass fiber cloth according to any one of claims 1 to 10, characterized in that: The steps include: Add a certain amount of water into the container, and add the water-soluble polyester main film-forming agent under stirring; Raise the temperature to 50°C-90°C and keep the temperature constant for 30-60 minutes to form a first stable uniform slurry; Adding polypropylene glycol as an auxiliary film-forming agent, maintaining the temperature at least 30 minutes under stirring to form a second stable uniform slurry; Add combustion improver, lubricant, antistatic agent and defoamer, keep constant temperature for 20-40 minutes to form a third stable uniform slurry; Make up the remaining amount of water, control the constant temperature at 40°C-70°C, and obtain the slurry for electronic grade glass fiber cloth.

12. A glass fiber product having a glass fiber diameter of 9 microns or less produced by using the electronic grade glass fiber cloth slurry according to any one of claims 1 to 10.

13. Use of the glass fiber product according to claim 12 in the field of manufacturing copper clad laminates and printed circuit boards.

Citation Information

Cited By

  • Slurry for low-dielectric fiber cloth as well as preparation method and application of slurry

    CN122013524A